Exploring Cold Case Homicide Survivors’ Perceptions of and Relationships With Law Enforcement - Wellman, Ashley P. (Journal of interpersonal violence, 2021)
Given the nature of unsolved homicide, a complicated dynamic exists between survivors of cold case homicides and law enforcement personnel. The current study utilizes interviews with 24 survivors to explore the perceptions associated with this relationship. Employing a grounded theory framework, we find several themes depicted within these narratives that guide survivors’ overall perceptions of their relationship with law enforcement, including investigative and communication efforts. Results indicate that the survivors universally perceive original detectives were incompetent or ineffective in their original investigation, thus leading to the unsolved status of their case. Over time, secondary and current investigators were also perceived as unable to properly investigate, due to challenges such as insufficient evidence or simply not conducting a comprehensive examination of the case. Regardless of this negative view of police activity on the case, relationships were defined by the level and nature of communication survivors had with their detective. Families who felt listened to, included, and/or valued reported a positive relationship with police that allowed them to trust their case was in good hands. Participants who perceived communication to be secretive, misleading, or completely absent noted strained relationships and further disappointment. Survivors may adopt roles, such as investigator, spokesperson, or advocate, to help compensate for their perception that the case is not properly cared for by police. With regard to grief progress and health of cold case homicide survivors, it is possible treatment by law enforcement outweighs the significant of case resolution years after the homicide. Recommendations for more productive survivor/police interactions are included.